Endocannabinoid modulation of dopamine neurotransmission. (15th September 2017) - Covey, Dan P.; Mateo, Yolanda; Sulzer, David; Cheer, Joseph F.; Lovinger, David M.
Abstract: Dopamine (DA) is a major catecholamine neurotransmitter in the mammalian brain that controls neural circuits involved in the cognitive, emotional, and motor aspects of goal-directed behavior. Accordingly, perturbations in DA neurotransmission play a central role in several neuropsychiatric disorders. Somewhat surprisingly given its prominent role in numerous behaviors, DA is released by a relatively small number of densely packed neurons originating in the midbrain. The dopaminergic midbrain innervates numerous brain regions where extracellular DA release and receptor binding promote short- and long-term changes in postsynaptic neuron function. Striatal forebrain nuclei receive the greatest proportion of DA projections and are a predominant hub at which DA influences behavior. A number of excitatory, inhibitory, and modulatory inputs orchestrate DA neurotransmission by controlling DA cell body firing patterns, terminal release, and effects on postsynaptic sites in the striatum. The endocannabinoid (eCB) system serves as an important filter of afferent input that acts locally at midbrain and terminal regions to shape how incoming information is conveyed onto DA neurons and to output targets. In this review, we aim to highlight existing knowledge regarding how eCB signaling controls DA neuron function through modifications in synaptic strength at midbrain and striatal sites, and to raise outstanding questions on this topic. This article is part of the Special Issue entitled "A New Dawn in Cannabinoid Neurobiology". Highlights: The endocannabinoid system controls synaptic transmission via feedback inhibition. Cannabinoid receptors modulate excitatory and inhibitory synaptic plasticity. Endocannabinoids control dopamine neurotransmission at midbrain and forebrain loci. Endocannabinoids filter dopamine input onto downstream targets.